2021
DOI: 10.3390/healthcare9111521
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers of Physical Activity Participation in Individuals with Intellectual Disability—A Systematic Review

Abstract: Individuals with intellectual disability (ID) tend to have a sedentary lifestyle, with low physical fitness and an increased risk of chronic diseases. One reason for the prevalence of a sedentary lifestyle is the existence of barriers to participation in physical activity (PA). The purpose of this systematic review is to update knowledge about the perceived barriers of PA participation in individuals with ID. Electronic searches were carried out in the PubMed, Scopus, SPORTDiscus and Web of Science databases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In this way, action can be taken to adjust the provision of PA to their motivations and take action to minimise the barriers they perceive. Possibly, due to the importance of these results, previous studies have analysed the motives for and barriers to the practice of PA both in people with a disability who are not habitual practitioners of PA or sport [25][26][27] and in sportspeople or habitual practitioners of PA with a disability in different modalities, at different competitive levels and with different impairments [28][29][30][31][32][33]. Moreover, it has been shown that there are significant differences in the perception of barriers between different disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, action can be taken to adjust the provision of PA to their motivations and take action to minimise the barriers they perceive. Possibly, due to the importance of these results, previous studies have analysed the motives for and barriers to the practice of PA both in people with a disability who are not habitual practitioners of PA or sport [25][26][27] and in sportspeople or habitual practitioners of PA with a disability in different modalities, at different competitive levels and with different impairments [28][29][30][31][32][33]. Moreover, it has been shown that there are significant differences in the perception of barriers between different disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, several factors may be contributing to the decrease in the number of barriers to the practice of physical activity [ 45 ] and the increase in the number of people enrolled in this practice [ 46 ], which positively impacts the number of people participating in the PG and performance indicators. Although the interest in the psychological skills of athletes started in the 1980s [ 47 ], the development of psychological skills training programs in Paralympic sports is recent [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is a complex occupation involving integration between psychological, social, cultural, environmental and physical factors, all of which need to be fully understood to support safe and sustained client engagement (Biddle et al , 2015). When working with people with intellectual disabilities with high support needs, this complexity is further increased, highlighting the need for additional education and training of allied health and fitness professionals working with this population (Bodde and Seo, 2009; Bossink et al , 2017; Cocks et al , 2018; Jacinto et al , 2021).…”
Section: Core Elements To Cover In Trainingmentioning
confidence: 99%
“…For allied health and fitness professionals, it is important to understand how the disability and health systems interconnect, key points of transition and how to work with interdisciplinary teams whilst working within a trauma informed framework. For example, education for certificate trained fitness professionals should involve guidance on how to collaboratively work with allied health professionals (occupational therapists, psychologists, physiotherapists, exercise physiologists) to ensure that their service is delivered in a way that is considerate of the individual’s physical and emotional safety (Jacinto et al , 2021).…”
Section: Core Elements To Cover In Trainingmentioning
confidence: 99%
See 1 more Smart Citation